Managing Foreign Exchange Rate Exposure A Case Study in Sinochem International Corporate - Ru, Qing (2008)
This dissertation is purposed to seek an exploration on the measurement and management foreign exchange exposure and the application in China. Although China has a tremendous improvement on economy in the recent three decades, its financial derivatives market is still undeveloped. Limited available derivatives constrain the corporate foreign exchange exposures management. A case study of Sinochem International Corporation is present for the research. By examining the firm's hedging data, the motivation and objective of the foreign exchange is disclosed, and the techniques employed by the firm are effective for managing the foreign exchange exposure. This dissertation also suggests a well-structured and holistic strategy involving the financial, business and market environment is a crucial factor for exchange exposure management.